The diagnosis of hypersensitivity to antibiotics is rarely confirmed by allergy work‐up in cystic fibrosis patients. Issue 4 (21st January 2020) - Braun, Camille; Reix, Philippe; Durieu, Isabelle; Nove‐Josserand, Raphaele; Durupt, Stéphane; Ohlmann, Camille; Mainguy, Catherine; Nicolas, Jean‐François; Nosbaum, Audrey; Jubin, Virginie
Abstract: Cystic fibrosis (CF) patients receive many antibiotic treatments for recurrent respiratory infections and frequently report antibiotic hypersensitivity reactions (HSRs). In this retrospective study, medical records of CF patients were reviewed to clarify the clinical features, the culprit antibiotics, and the prevalence of antibiotic HSRs in the CF population. From 601 CF patients, 95 suspected antibiotic HSRs occurred in 60 patients (prevalence of 10.0%). β‐Lactams were the most common inducers, but cotrimoxazole was also frequently involved. Seventy‐six of 95 suspected HSRs were assessed by allergy workup including skin tests (43/76 reactions) and/or drug reintroduction as a full course of the culprit antibiotic (73 of 76 reactions). From the 43 suspected HSRs that were skin‐tested, only three had positive skin tests and were not subjected to drug readministration. All the other 73 suspected HSRs received a full course of the culprit antibiotic: HSR symptoms recurred in 10 of 73 cases and therefore were considered as confirmed antibiotic HSRs; for the remaining 63 suspected HSRs that did not relapse after drug readministration, the diagnosis of antibiotic HSRs was excluded. In summary, 13 of 76 suspected HSRs were confirmed as antibiotic HSRs. The prevalence of suspected and confirmed antibiotic HSRs in CF patients appears similar to that reported in the general population. Of note, most of the antibiotic suspected HSRs are not confirmed after allergology workup. A complete allergy workup appears therefore crucial to make a correct diagnosis and to avoid unnecessary contraindication of major antibiotics.